Tingkat Burnout Mahasiswa dalam Pembelajaran Daring Masa Pandemi COVID-19 - Sajodin Sajodin; Utari Suci Anjani; Perla Yualita (Jurnal Keperawatan Silampari, 2022)
This study aims to determine the burnout level of students in online learning during the COVID-19 pandemic. This study used a descriptive research design with a cross-sectional approach. The results showed that the emotional aspect, the physical fatigue aspect, the cognitive fatigue aspect, the loss of motivation aspect in the moderate category, and the emotional fatigue aspect were the highest while the physical fatigue aspect was the lowest. In conclusion, the burnout level of students in online learning during the COVID-19 pandemic is in the medium category. Keywords: Burnout, COVID-19 Pandemic, Online Learning